Development of pathophysiologically relevant models of sickle cell disease and β-thalassemia for therapeutic studies - Pragya Gupta; Sangam Giri Goswami; Geeta Kumari; Vinodh Saravanakumar; Nupur Bhargava; Akhila Balakrishna Rai; Praveen Singh; Rahul C. Bhoyar; V. R. Arvinden; Padma Gunda; Suman Jain; Vanya Kadla Narayana; et al. (Nature Communications, 2024)
Abstract Ex vivo cellular system that accurately replicates sickle cell disease and β-thalassemia characteristics is a highly sought-after goal in the field of erythroid biology. In this study, we present the generation of erythroid progenitor lines with sickle cell disease and β-thalassemia mutation using CRISPR/Cas9. The disease cellular models exhibit similar differentiation profiles, globin expression and proteome dynamics as patient-derived hematopoietic stem/progenitor cells. Additionally, these cellular models recapitulate pathological conditions associated with both the diseases. Hydroxyurea and pomalidomide treatment enhanced fetal hemoglobin levels. Notably, we introduce a therapeutic strategy for the above diseases by recapitulating the HPFH3 genotype, which reactivates fetal hemoglobin levels and rescues the disease phenotypes, thus making these lines a valuable platform for studying and developing new therapeutic strategies. Altogether, we demonstrate our disease cellular systems are physiologically relevant and could prove to be indispensable tools for disease modeling, drug screenings and cell and gene therapy-based applications.